Characterization of the Thermal Response of Munitions in Storage Exposed to Real and Arbitrary Weather Conditions. Issue 2 (18th January 2016) - Blecker, Ken; Hadim, Hamid
Abstract: The objective of this investigation is to characterize the thermal response of stored munitions exposed to real weather conditions in order to validate current test procedures as well as develop the ability to provide an estimate of the thermal exposure over the lifecycle of a munition. Currently, the thermal history of munitions in storage cannot be determined without continuous monitoring of individual items and there is no method to provide a detailed estimate of the exposure by analyzing existing data when continuous data was not collected. This work describes the experimental and initial numerical investigations of instrumented munitions in storage to characterize their thermal response. The numerical model has the capability to validate broad trends observed from the experimental data. For this investigation, data is being collected through field experiments of inert munitions instrumented with thermocouples that are collocated near a weather station. Data from field experiments are used to develop and validate the numerical model. The numerical model will save time and resources in future investigations of the thermal exposure of munitions in storage as well as advance the understanding of the implications of selecting a long term storage environment. At a fundamental research level, this work contributes to the advances in combined heat transfer by natural convection and radiation inside a 3D enclosure combined with external forced convection and radiation. The numerical model includes several features including heat transfer to the enclosure by solar radiation, conduction, and forced convection, heat transfer between the enclosure container walls and the projectiles by radiation, conduction, and natural convection, heat transfer within the projectile by conduction, distributed thermal energy storage in projectiles, and transient temperature boundary condition at the enclosure walls. Abstract :